2021
DOI: 10.3390/foods10010142
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Potential of Pine Needles: A Systematic Study on the Essential Oils and Extracts of 46 Species of the Genus Pinus

Abstract: The antioxidant activity of the essential oils, as well as of the organic and hydroethanolic extracts, of the fresh needles of 54 pine taxa was evaluated using the peroxy-oxalate and luminol chemiluminescence assays. Among all evaluated essential oils, P. canariensis and P. attenuata displayed the highest levels of activity. P. contorta var. murrayana, followed by P. nigra var. caramanica, exhibited the highest antioxidant capacity among the organic extracts, while the most active hydroethanolic extract was th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 48 publications
0
13
0
1
Order By: Relevance
“…Pinus is a well-known source of antioxidants, mainly phenolic compounds. 24 Lately, the antimicrobial, antidiabetic, anti-inflammatory, and cytotoxic properties of P. halepensis have been reported. [25][26][27][28] To the best of our knowledge, P. halepensis bark extract has not been studied before with prostate cancer or prostate cancer PDT.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pinus is a well-known source of antioxidants, mainly phenolic compounds. 24 Lately, the antimicrobial, antidiabetic, anti-inflammatory, and cytotoxic properties of P. halepensis have been reported. [25][26][27][28] To the best of our knowledge, P. halepensis bark extract has not been studied before with prostate cancer or prostate cancer PDT.…”
Section: Discussionmentioning
confidence: 99%
“…Pinus is a well‐known source of antioxidants, mainly phenolic compounds 24 . Lately, the antimicrobial, antidiabetic, anti‐inflammatory, and cytotoxic properties of P. halepensis have been reported 25–28 .…”
Section: Discussionmentioning
confidence: 99%
“…Pine trees are widely used to produce various wood and cellulose products, but often overlooked are the needles of these trees. In scientific literature, pine needles have been studied to monitor atmospheric pollution [ 14 , 15 , 16 ], while needle extracts are used in various medications and supplements [ 17 , 18 ]. Natural waxes are a byproduct of this extraction, often treated as waste.…”
Section: Introductionmentioning
confidence: 99%
“…reported that pine needles has many physiological, pharmacologial activities and it is a good source of antioxidants and phenolic compounds including phenolic acids, flavonoids, procyanides [1], [2]. Pine trees (Pinus densiflora) have shown a wide range of biologically functional activities and many methods have been applied for phenolic compounds extraction from pine trees.…”
Section: Introductionmentioning
confidence: 99%